2019
DOI: 10.3892/etm.2019.8249
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated miRNA-324-5p aggravates neuronal injury induced by oxygen-glucose deprivation via modulating RAN

Abstract: Differentially expressed miRNAs in the GEO profile of ischemic stroke were analyzed to clarify the specific role of microRNA-324-5p (miRNA-324-5p) in ischemic stroke and the potential mechanism. After screening out miRNA-324-5p, its level in peripheral blood of stroke patients and in vitro oxygen-glucose deprivation (OGD)-induced primary rat neurons was determined by quantitative real-time polymerase chain reaction (qRT-PCR). Regulatory effects of miRNA-324-5p on viability, and apoptosis of OGD-induced neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…We primarily identified that Ran could be targeted by miR-324-5p, which was consistent with previous study. 43 Small GTPase Ran was a carcinogenic protein. Several miRNAs, including miR-802, miR-2, miR-197, miR-203 could directly bind to Ran to modulate cancer cell behaviors in cancers, 15 , 44–47 which indicated that Ran involved in the regulation of malignant behaviors in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…We primarily identified that Ran could be targeted by miR-324-5p, which was consistent with previous study. 43 Small GTPase Ran was a carcinogenic protein. Several miRNAs, including miR-802, miR-2, miR-197, miR-203 could directly bind to Ran to modulate cancer cell behaviors in cancers, 15 , 44–47 which indicated that Ran involved in the regulation of malignant behaviors in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that thrombolysis has a strict time window limitation [4]. Once it is exceeded, regaining blood ow can worsen brain injury, known as cerebral ischemia-reperfusion injury (CIRI) [5].…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is classi ed clinically as ischemic or hemorrhagic, with 80% occurring as ischemic strokes [2]. At present, thrombolysis and mechanical thrombectomy are well established treatments of acute ischemic stroke [3].However, it is important to note that thrombolysis has a strict time window limitation [4]. Once it is exceeded, regaining blood ow can worsen brain injury, known as cerebral ischemia-reperfusion injury (CIRI) [5].…”
mentioning
confidence: 99%
“…With regard to miR-324-5p, which we show to be downregulated in HIV lipodystrophy, this miRNA has also been shown to be downregulated in circulating sEVs of patients with type 2 diabetes mellitus while demonstrating an inhibitory effect on diabetes-related inflammation ( 31 ). miR-324-5p overexpression has been linked to enhanced glucose uptake in oxygen glucose–deprived neurons ( 32 ) and has been reported to promote Wnt signaling ( 33 ). Consistent with this, we found downregulated Wnt signaling in adipocytes following treatment with anti–miR-324-5p.…”
Section: Discussionmentioning
confidence: 99%